Similarity effect on the perception of two simultaneously presented figures - Gurčinienė, Ona; Šoliūnas, Alvydas (Psichologija, 1999)
Relatedness of the analysis of a few simultaneously presented objects in the visual field was investigated in the psychophysical experiment on human subjects. Test stimuli were plane nonsemantic geometrical figures composed on a basis of 4 x 3 matrix. Five groups of figure pairs with different degree of reciprocal similarity were presented for recognition under the backward masking conditions. Exposition duration of test figures varied individually from 400 to 3000 ms. Masking of test figures was followed by a special marker that indicated which one of two test figures must be detected in the subsequently presented table that included all 12 test figures. Experimental data revealed two groups of subject. The same recognition accuracy for the pairs of identical and different figures as well as no effect of similarity on the recognition of different figures characterised the results of the first group of subjects. The second group of subjects recognised identical figures more accurately than different ones and the recognition of different figures had direct dependence on their similarity - the more similar the figures were, the more accurately they were recognised. Experimental results were interpreted on the basis of different analysis strategies applied by different subejcts.